2015
DOI: 10.3390/fib3040394
|View full text |Cite
|
Sign up to set email alerts
|

Using Mechanical Alloying to Create Bimetallic Catalysts for Vapor-Phase Carbon Nanofiber Synthesis

Abstract: Carbon nanofibers were generated over bimetallic catalysts in an atmospheric pressure chemical vapor deposition (APCVD) reactor. Catalyst compositions of Fe 30 at%, Cu and Ni 30 at% and Cu were mechanically alloyed using high-energy ball milling over durations of 4,8,12,16, and 20 h. The catalyst powders were then used to produce carbon nanofibers in ethylene and hydrogen (4:1) at temperatures of 500, 550, and 600 °C. The microstructures of the catalysts were characterized as a function of milling time as well… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 75 publications
0
8
0
Order By: Relevance
“…% Cu catalyst was chosen for its ease of processing, low cost, and high selectivity toward nanofiber growth. In kinetic studies [31], it resulted in a deposition rate of $5000% mass gain per hour of reaction and yields a fiber mass dominated by nanofibers approximately 100 nm in diameter with a high degree of integration, even during unconstrained growth. The growth rate observed in this work was $ 2100% mass gain per hour of reaction (e.g., 20 mg of catalyst yields 2 g of carbon over about 5 h).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…% Cu catalyst was chosen for its ease of processing, low cost, and high selectivity toward nanofiber growth. In kinetic studies [31], it resulted in a deposition rate of $5000% mass gain per hour of reaction and yields a fiber mass dominated by nanofibers approximately 100 nm in diameter with a high degree of integration, even during unconstrained growth. The growth rate observed in this work was $ 2100% mass gain per hour of reaction (e.g., 20 mg of catalyst yields 2 g of carbon over about 5 h).…”
Section: Resultsmentioning
confidence: 99%
“…Each alloy was milled with 1 wt.% stearic acid (reagent grade, 95%) to prevent cold welding during the 4 h milling duration (see Ref. [31], for more information on this preparation method). All starting materials were obtained from Sigma-Aldrich and used without modification.…”
Section: Methodsmentioning
confidence: 99%
“…Each alloy was milled with 1 wt % stearic acid to prevent cold welding. Separate powder charges were milled under argon for 5,10,15,20,30,45,60,75,90,120,180 and 240 min, in that order, without cleaning the vial in between runs to reduce contamination from the vial and milling media (stainless steel). Pure nickel was milled under the same conditions as a control.…”
Section: Materials Processingmentioning
confidence: 99%
“…Pure nickel was milled under the same conditions as a control. Previous studies [20,21] demonstrated pure copper to have negligible catalytic properties for CNF synthesis and was not used as a control. Ni and Ni 30 at % Cu were also used in "unmilled" form as an experimental control.…”
Section: Materials Processingmentioning
confidence: 99%
See 1 more Smart Citation